A Conceptual Framework of Internet Contributions to Young Adult Entrepreneurship - Dy, Angela Carmina Martinez (2010)
This paper develops the basis of a conceptual framework of the effects of the Internet and World Wide Web on entrepreneurship in the present day. As academic literature suggests Web experience and familiarity with search tools can contribute significantly to usage for beneficial purposes, and journalists credit the Internet for rising numbers of young Internet entrepreneurs due to the various types of access it enables, young adult Internet users are the focus of the paper. In July 2010, a survey of 104 18-35 year olds was conducted using the Facebook social networking platform with a follow-up qualitative questionnaire sent by e-mail. Years of usage, hours of use per day, amount of time used for work or business, and entrepreneurial intention were tested in a logistic regression analyses for their bearing on online and offline idea generation and implementation. Usage statistics, along with additional independent and control variables both Internet and non-Internet related, were also tested in a probit analysis for their contributions to entrepreneurial intention. Significant relationships were found between use of the Internet for work or business and opportunity pursuit as well as between the importance of the Internet to one’s most significant business idea and entrepreneurial intention. Survey results point to the rise of a new class of young adult entrepreneurs and potential entrepreneurs as a result of the ways in which the Internet has changed the “rules of the game.” Various implications for future research, educators and policymakers are suggested to further the reach of the Internet for entrepreneurial purposes, promote access and the development of digital literacy and online skills among the information poor.